1973
DOI: 10.1128/aac.4.4.383
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Ampicillin or Vancomycin Combined with Gentamicin or Streptomycin Against Enterococci

Abstract: Minimum inhibitory and bactericidal concentrations of four antibiotics and their combinations were determined for 38 strains of enterococci by a microtitration tube dilution technique. The drugs were ampicillin, vancomycin, gentamicin, and streptomycin; the combinations were ampicillin-gentamicin, ampicillin-streptomycin, vancomycin-gentamicin, and vancomycin-streptomycin. At achievable serum concentrations, ampicillin alone killed 60% of strains, whereas combination with streptomycin increased this to 90% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 10 publications
3
32
0
1
Order By: Relevance
“…Strains of E. faecalis exhibit low-level resistance to aminoglycosides (3) and to lincomycin and clindamycin (10); they exhibit an intermediate level of resistance to penicillins and cephalosporins (15). In addition, most clinical isolates exhibit tolerance to the bactericidal effects of cell wall-active agents (7,12). Alarming trends in recent years include the emergence of strains with high-level resistance to aminglycosides (11), the appearance of 3-lactamase-producing isolates (14), and the discovery of strains that are resistant to vancomycin (19).…”
mentioning
confidence: 99%
“…Strains of E. faecalis exhibit low-level resistance to aminoglycosides (3) and to lincomycin and clindamycin (10); they exhibit an intermediate level of resistance to penicillins and cephalosporins (15). In addition, most clinical isolates exhibit tolerance to the bactericidal effects of cell wall-active agents (7,12). Alarming trends in recent years include the emergence of strains with high-level resistance to aminglycosides (11), the appearance of 3-lactamase-producing isolates (14), and the discovery of strains that are resistant to vancomycin (19).…”
mentioning
confidence: 99%
“…Resistance to penicillin killing (in the absence of ,B-lactamase) is a trait that distinguishes enterococci from other streptococci that commonly cause endocarditis, e.g., the viridans group streptococci (8,16). Although several studies have documented the resistance of enterococci to killing by ,f-lactams (11,23) and one previous study found enterococci resistant to killing by vancomycin (6) (14), another study of S. bovis did not reveal defective killing with ,Blactams (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, with penicillin and aminoglycoside resistance rates increasing vanconiycin is now often used to treat enterococcal infections. VRE were extremely rare before 1988 with just two isolates (MIC greatern than 100 m g/mL) documented in the previous two decades (16,17). In 1988, VRE began to emerge as a clinical concern, with the description of 55 clinical isolates of VRE (seven Enterococcus faecalis and 48 E faecium) (MICs greater than 64 m g/mL) from 22 British patients with renal impairment (18).…”
Section: Discussionmentioning
confidence: 99%